Establishment and cutting regimes of alfalfa and Paspalum guenoarum alone in mixtures - Costa, Newton de Lucena; Saibro, João Carlos de (Pesquisa Agropecuaria Brasileira, 2014)
Under field conditions, at the Estação Experimental Agronômica of the Federal University of Rio Grande do Sul, at Guaíba, RS, in southern Brazil, the effect of sowing methods of alfalfa and P. guenoarum Arech. alone, seeded either broadcast or in rows, and in mixtures, broadcast and in alternate rows, was evaluated. Forage was harvested at the vegetative and flowering alfalfa growth stages, at 5 cm and 10 cm cutting heights. Cutting forage at the alfalfa flowering stage and at 5 cm resulted in higher dry matter (DM) yields of alfalfa, weed and total mixture components. The mixtures were more efficient in DM production and provided better weed control as compared to the grass or legume species seeded alone. Harvesting at vegetative stage resulted in higher forage crude protein content. There was a tendency for the 10 cm stubble height to increase the percentage of grasses, while for the 5 cm stubble the tendency was to increases alfalfa and weeds in the mixtures. The sowing methods did not affect DM yields of alfalfa and P. guenoarum alone, as well as the DM yields of the forage mixtures.
Keywords: Medicago sativa; dry matter yield; crude protein; clipping height